EMPIRICAL RESEARCH OF THE CHARACTERISTICS OF DREAMS OF WOMEN WHO FEEL LONELINESS (Psychology Travelogs, 2023)
The article presents the results of an empirical study of the characteristics of the dreams of women experiencing loneliness. For this, two groups of methods were used: 1) to study loneliness: diagnostic questionnaire «Loneliness»; questionnaire «Self-assessment of mental states» by H. Eysenk; questionnaire «I and Loneliness» (L. Podkorytova, I. Makaruk); the method «Diagnosis of the level of subjective feeling of loneliness» (D. Russell and M. Ferguson); 2) for the study of dream images – author’s developments: the questionnaire «Emotional features in dreams» (O. Zaslavska, L. Podkorytova), the «Emotional tonality» method (O. Zaslavska). A description of these author's developments is presented in the article.The conducted empirical research made it possible to make two groups of women according to the level of loneliness: group A) women who feel loneliness superficialy; group B) women who feel loneliness deeply. By the comparative analysis in these groups it was founded the differences in the images of dreams of women, depending on their feeling of loneliness.It was found that in the group of women who feel loneliness deeply, there are more subjects who experience anxiety, frustration, aggressiveness and rigidity than in the group of women who feel loneliness superficialy.It was determined that the following images are inherent in the dreams of women who feel loneliness deeply: the superiority of passive actions over active ones, the predominance of negative emotions (fear, despair, anger, sadness), and their dominance over positive ones; for natural phenomena, the leading images are night, darkness and cold. On the contrary, active actions, pleasant emotions and pleasant natural images (sun, warmth etc.) prevail among women who feel loneliness superficialy. According to the relationship criterion, no significant differences were found in the studied groups of women.Prospects for further research are seen in expanded samples and diagnostic tools, comparison of features of dreams in women of different ages, as well as in men experiencing loneliness and comparison of the obtained results by age and gender.
Keywords: loneliness; feeling; dreams; emotions; actions; relationships; images